"Niveles de inclusión de harina de Tithonia diversifolia en el engorde de Cavia porcellus L. sexados". - Laborde Bazurto, Lisbeth Thays (2020)
The research was carried out at the Experimental Campus "La María" of the Quevedo State Technical University (UTEQ), located at km. 7½ of the Quevedo-El Empalme road, Mocache Canton, Los Ríos Province, whose geographical location is 1 ° 3'18 ”south latitude and 79 ° 25 '24' 'west longitude, at a height of 77.60 masl , with a duration of 42 days. The objectives being: To determine the productive behavior of sexed guinea pigs (Cavia porcellus L.), fed with different levels of inclusion (0; 10; 20; 30 and 40%) of buttercup (Thitonia diversifolia)) in the diet and establish the profitability of the treatments. A factorial arrangement 2 (sex) x 5 (inclusion levels) was applied, within a Completely randomized Block Design (DBCA), the initial weight of the experimental units (UE) was blocked, with four repetitions. Tukey's test (P≤0.05) was used to determine the statistical differences. 40 guinea pigs (20 males and 20 females) 35 days old, with an average weight of 248.48 ± 28.88 g, were used. The final weight (g), feed consumption (g), weight gain (g), feed conversion index, carcass weight (g), carcass yield (%) and profitability (%) were evaluated. The sexual condition (males-females) significantly influenced (P˂0.05) on the final weight, weight to the carcass and the performance to the carcass, with the females achieving the best responses (707.85 g, 503.10 g and 71.06%, respectively). ). Inclusion levels did not influence (P˃0.05) on weight gain, feed intake and feed conversion index. However, with 20% inclusion, the highest (P˂0.05) final weight (731.50 g), carcass weight (534.13 g) and carcass yield (72.98%) were recorded. The highest profitability is obtained by fattening male and female guinea pigs with 20 and 30% inclusion of buttercup in the diet (59.16 and 56.45%, respectively). The results achieved allow us to suggest the inclusion of pro button flour in diets for fattening guinea pigs on the Ecuadorian coast. Key words: nutrition, feeding, forages, bushes, diets.